Learn BlackBerry 10 app development : a Cascades-drive approach - Ludin, Anwar (Apress Open, 2014)
The purpose of this book is to teach you how to leverage the BlackBerry 10 Cascades framework in order to create rich native applications. The book is directed at prior BlackBerry developers, developers wishing to learn to program their app for the new BlackBerry paradigm and those interested in porting existing iOS or Android apps to this framework. The book gives you a solid introduction to using QML and JavaScript and C++ and Qt to create BlackBerry 10 apps clearly and efficiently. Along the way, you will learn to create a visually enticing user experience with Cascades and QML. From configuring the SDK to publishing your app, you will rapidly learn many of the best practices and techniques to develop successful BlackBerry apps.